Hyponatremic Events Occurring in Hypertensive Patients While Taking Thiazide Diuretic: Cross-Sectional Study - Thakur , Sanjay Kumar; Yadav, Shree Narayan; Dhakal, Sukhesh Purush; Katwal, George Bush Jung; Sah, Anil Kumar; Paudel, Bishnu Dutta (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Hyponatremia is common with thiazide. We evaluated how commonly hyponatremia occurs among Nepalese hypertensive patients while they are kept on thiazide. Method: It was a cross-sectional study, conducted from 2017-March to 2018-March at Bir hospital and Annapurna Neurological Institute & Allied Sciences, Kathmandu. Data on demography, Thiazide diuretics, use of other medicines and laboratory investigation were obtained from all the hypertensive patients. Four hundred twenty-three patients who met the inclusion criteria i.e., Adult hypertensive patients while on Thiazide diuretic with or without Ca+ Channel blocker (CCB), with or without Angiotensin Receptor Blocker/Angiotensinogen converting enzyme inhibitor (ARB/ACEI) and taking diet orally were enrolled in this study. Conditions like SIADH (syndrome of Inappropriate Anti Diuretic Hormone), congestive heart failure, liver failure, renal failure, or pneumonia and drugs likely to cause hyponatremia were excluded. Serum osmolality was calculated and patients having normal osmolality i.e., 280-300 mos/l was included. Hyponatremia was categorized based on serum level of sodium as Mild (120-134 mmol/l), Moderate (110- 119mmol/l), and Severe (<110mmol/l and/or Symptoms like seizure, disorientation, lethargy, loss of consciousness). Chi-squared tests were used for comparisons between categorical data and multiple regression analysis was used to measure interrelationships between variables in the study population. Result: A total of four hundred twenty-three (n=423) hypertensive patients were included. Hyponatremia was found in 380 (89.8%) cases. We found 2.9% mild, 74.7% moderate and 22.4% severe cases of hyponatremia. Hyponatremia was commonly found among thiazide users in combination with ARB/ACEI and/or CCB or alone (254/380=66%) (p=0.02). Hyponatremia was frequent (57.6%) among 50-69 years of age (p=0.001). Dietary Salt restriction was practiced by 79.2% of hyponatremia cases (p=0.014) (Table 1). Conclusion: Hyponatremia was seen frequent among hypertensive patients taking thiazide.